Controlled Blood Pressure in Iranian Patients: A Multi-Center Report - Sadeghi, Ezzatollah (Glob J Health Sci, 2016)
We decided to determine the percentage of hypertensive patients whose blood pressure (BP) measurements were within recommended controlled range and to identify predictive factors for controlled BP. In this study carried out in 2014, 280 patients were included consecutively through sampling from both university and private medical centers/pharmacies in four Iranian cities. Demographic data as well as information about duration of HTN and prescribed medications, admission to emergency department (ED) because of HTN crisis, comorbidities, and control of HTN during the last 6 months by a healthcare provider were gathered. Adherence to anti-hypertensives was also determined using the validated Persian version of the 8-item Morisky Medication Adherence Scale (MMAS-8). Controlled BP was defined as systolic BP< 140 and diastolic BP< 90 mmHg in non-diabetics and < 130/80 mmHg in diabetics. Of 280 patients, 122 subjects (43.6%) had controlled BP. Among 55 diabetics, only two patients (3.6%) had controlled BP. Multiple logistic regression revealed the following variables as significant predictors of controlled BP: higher MMAS-8 score (adjusted odds ratio (OR)= 1.19, P= 0.03), fewer number of comorbid conditions (adjusted OR= 0.71, P = 0.03), having occupation as clerk/military personnel (adjusted OR= 1.03, P= 0.04), and not having history of ED admission during the last 6 months because of HTN crisis (adjusted OR= 2.11, P= 0.01). Considerable number of the studied patients had uncontrolled BP. Regarding the dramatic consequences of uncontrolled high BP in long term, it is advisable that careful attention by health care providers to the aforementioned factors could raise the likelihood of achieving controlled BP.